Hs1Cas12a and Ev1Cas12a confer efficient genome editing in plants - Li, Gen; Zhang, Yingxiao; Dailey, Micah; Qi, Yiping (Frontiers in Genome Editing, 2023)
Cas12a, also known as Cpf1, is a highly versatile CRISPR-Cas enzyme that has been widely used in genome editing. Unlike its well-known counterpart, Cas9, Cas12a has unique features that make it a highly efficient genome editing tool at AT-rich genomic regions. To enrich the CRISPR-Cas12a plant genome editing toolbox, we explored 17 novel Cas12a orthologs for their genome editing capabilities in plants. Out of them, Ev1Cas12a and Hs1Cas12a showed efficient multiplexed genome editing in rice and tomato protoplasts. Notably, Hs1Cas12a exhibited greater tolerance to lower temperatures. Moreover, Hs1Cas12a generated up to 87.5% biallelic editing in rice T0 plants.Both Ev1Cas12a and Hs1Cas12a achieved effective editing in poplar T0 plants, with up to 100% of plants edited, albeit with high chimerism. Taken together, the efficient genome editing demonstrated by Ev1Cas12a and Hs1Cas12a in both monocot and dicot plants highlights their potential as promising genome editing tools in plant species and beyond.